Proceedings of the 20th ACM International Conference on Intelligent Virtual Agents 2020
DOI: 10.1145/3383652.3423908
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personality on Nonverbal Behavior Generation

Abstract: To realize natural-looking virtual agents, one key technical challenge is to automatically generate nonverbal behaviors from spoken language. Since nonverbal behavior varies depending on personality, it is important to generate these nonverbal behaviors to match the expected personality of a virtual agent. In this work, we study how personality traits relate to the process of generating individual nonverbal behaviors from the whole body, including the head, eye gaze, arms, and posture. To study this, we first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Some interesting developments we observe in the recent work are the shift toward neural network [21,30,19,16,1,23,39,31], the use of adversarial learning [19,16], and the use of word embedding [1,23,31]. Neural network has been successful in recent years, which therefore makes it into a reasonable choice for machine learning problems.…”
Section: Related Workmentioning
confidence: 99%
“…Some interesting developments we observe in the recent work are the shift toward neural network [21,30,19,16,1,23,39,31], the use of adversarial learning [19,16], and the use of word embedding [1,23,31]. Neural network has been successful in recent years, which therefore makes it into a reasonable choice for machine learning problems.…”
Section: Related Workmentioning
confidence: 99%
“…Prior studies have shown that human-centered traits are characterized by specific non-verbal (and specifically, head-motion) behaviors; e.g., an upright posture maintaining eye-contact conveys high Conscientiousness, while gaze avoidance is indicative of low Conscientiousness [16,18]. Likewise, frequent head nodding is seen as courteous and agreeable behavior, while head shaking and frowning indicates a cold demeanor [17,26]. Kinemes inherently enable discovery of temporal head-motion patterns characteristic of a given trait, and sequence learning methods such as Hidden Markov Models (HMMs) and Long-short term memory (LSTM) networks can be employed to learn these latent temporal signatures for continuous or categorical trait prediction.…”
Section: Trait Prediction From Kinemesmentioning
confidence: 99%
“…The head motion time-series is then unsupervisedly decomposed into a kineme sequence comprising elementary head motion units. This decomposition enables discovery of kinemes characteristic of a target trait, e.g., head nodding is typical of courteous or sympathetic behavior [17,26]. In addition to head motion, we also utilize action units (AUs) which encode facial motion and expressions, for trait prediction.…”
mentioning
confidence: 99%
“…However, the authors do not provide a detailed quantitative mapping of personality dimensions to non-verbal behaviour. Ishii et al (2020) have taken a machine learningbased approach to investigate the link between personality and non-verbal behaviour. Based on an annotated corpus, they have trained a model to generate non-verbal behaviour associated with speech.…”
Section: Related Workmentioning
confidence: 99%